RGC-32 facilitates pancreatic cancer via activating Wnt/β-catenin signaling: RGC-32 promotes pancreatic cancer via Wnt/β-catenin signaling - He, Jinli; Yang, Guihong; Cao, Ronglai; Zhu, Liang (Cellular and Molecular Biology, 2023)
Longitudinal studies have indicated the facilitating effect of RGC-32 during diverse disease progression including pancreatic cancer, yet the systematic and detailed effect of RGC-32 during pancreatic cancer is largely unknowable. For this purpose, we took advantage of the pancreatic cancer cell line (BXPC3) with RGC-32 expression and then modulated its expression by lentivirus-mediated knockdown (shRGC-32) and overexpression (pcDNA-RGC-32). To verify the effect of Wnt/β-catenin signaling in RGC-32-based tumorigenicity, we added the agonist CT99021 to the shRGC-32 BXPC3 cell line and pancreatic cancer mouse model. The deficiency in cellular vitality (cell survival, apoptosis, cell cycle) and migration of BXPC3 were sharply rescued by shRGC-32 in vitro. Notably, the aforementioned phenotypes as well as the expression pattern of EMT-associated biomarkers of BXPC3 with shRGC-32 expression could largely rescued by the agonist of Wnt/β-catenin in vitro and in vivo. Our data indicated the facilitating effect of RGC-32 upon pancreatic cancer cell line and mouse model via activating the Wnt/β-catenin signaling, which collectively suggested the feasibility of RGC-32 as a potent diagnostic and therapeutic target of pancreatic cancer in the future.